2022
DOI: 10.1155/2022/1824166
|View full text |Cite
|
Sign up to set email alerts
|

The Long Noncoding RNA MEG3 Retains Epithelial-Mesenchymal Transition by Sponging miR-146b-5p to Regulate SLFN5 Expression in Breast Cancer Cells

Abstract: More and more studies have shown that long noncoding RNAs (lncRNAs) play essential roles in malignant tumors. The lncRNA MEG3 serves as a crucial molecule in breast cancer development, but the specific molecular mechanism needs to be further explored. We previously reported that Schlafen family member 5 (SLFN5) inhibits breast cancer malignant development by regulating epithelial-mesenchymal transition (EMT), invasion, and proliferation/apoptosis. Herein, we demonstrated that MEG3 was downregulated in pan-canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…It has been established that lncRNAs may function as oncogenes or tumour suppressors in the progression and metastasis of breast cancer and have great potential as diagnostic and prognostic biomarkers [22]. An increasing number of studies have revealed that MEG3 is downregulated and represses cell proliferation, migration, and invasion, and induces apoptosis in breast cancer cells [23][24][25][26][27]. The present study confirmed the downregulation of MEG3 in both tumour tissue and breast cancer cells, showing consistent effects on cell proliferation, migration, invasion, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that lncRNAs may function as oncogenes or tumour suppressors in the progression and metastasis of breast cancer and have great potential as diagnostic and prognostic biomarkers [22]. An increasing number of studies have revealed that MEG3 is downregulated and represses cell proliferation, migration, and invasion, and induces apoptosis in breast cancer cells [23][24][25][26][27]. The present study confirmed the downregulation of MEG3 in both tumour tissue and breast cancer cells, showing consistent effects on cell proliferation, migration, invasion, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it maintains and restores the epithelial morphology of breast cancer cells by downregulating ZEB1 transcription, thereby preventing EMT in breast cancer. Li et al (35), through bioinformatics analysis of TCGA data, discovered that miR-146b-5p can bind to the SLFN5 3'UTR and MEG3, demonstrating that MEG3 positively regulates SLFN5 expression and inhibits breast cancer development through sequestration of miR-146b-5p (see Figure 1). MEG3 is downregulated in various cancers and positively correlates with SLFN5 expression in breast cancer (36, 37).…”
Section: Slfn5 Protein and Its Functionsmentioning
confidence: 99%